Phase transitions in complex fluids - Toléedano, P (World Scientific, 1998)
Includes bibliographical references and indexes.; This important and timely book deals with the theoretical and experimental investigation of the phase transitions which occur in complex fluid systems, namely lyotropic systems, microemulsions, colloids, biological membranes, and ferrofluids. It contains 17-odd review papers from the major contributors to this rapidly growing field of research, summarizing the main results obtained in the description and understanding of the phase transitions taking place between the isotropic, nematic, cholesteric, lamellar, hexagonal, and cubic mesophases of complex fluids